An investigation into faculty developers' experiences in the process of assisting faculty in teaching with technology in higher education: a multiple case study - Edouard, Gusman (My University, 2025)
Many higher education institutions (HEIs) struggle with preparing their faculty to teach with technology in diverse teaching settings, be it traditional, hybrid, or online. Numerous studies examined how HEIs equipped faculty members (FM) to leverage technology tools in their teaching. However, most of these investigations gathered data from the perspectives of FMs. The literature has largely overlooked the pivotal roles of faculty developers (FD), professionals who assist faculty in leveraging technology in their teaching. This qualitative multiple-case study, guided by the Technological Pedagogical Content Knowledge (TPACK) Framework and the Awareness, Desire, Knowledge, Ability, Reinforcement (ADKAR) Change Management Model, examined the experiences of four FDs in assisting FMs to use technology for teaching and learning at two research-intensive universities. Findings revealed five major themes that capture FDs' experiences and perceptions of their work and roles. Precisely, this study revealed that: (a) change was a fundamental aspect of the FDs' work and role, (b) FDs' work assisting FMs to teach with technology was a complex, multifaceted process of navigating change to develop faculty's technological and pedagogical knowledge and skills, (c) FDs' experiences were multifaceted, defined by both professional opportunities and institutional challenges, (d) FDs worked to overcome role ambiguity and misconceptions to justify their value as academic partners and collaborators, and (e) various factors, including organizational structure, leadership support, and FD unit location on campus influenced FDs' work. Practical implications for educational programs that train FDs and HEI administrators who hire FDs are discussed. Recommendations for future studies are also provided.
Keywords: Educational technology integration; Technological pedagogical content knowledge; Higher education; Faculty developers; Faculty development; Change management